Low TB radio SAW sensors incorporating chirped transducers and reflectors for wireless pressure sensing applications - Pankratz, Thomas; Scherr, Holger; Reindl, Leonhard; Ruppel, Clemens; Weigel, Robert (1998 IEEE MTT-S International Microwave Symposium Digest, 1998)
We report on the design and performance of two basic SAW delay line structures developed for a wireless pressure sensing system operating at 434 MHz. The pressure sensor has been fabricated in all-quartz-package (AQP) technology with the SAW structures being placed on a diaphragm inside the hermetically sealed cavity. Both SAW structures show a linear phase although they both incorporate chirped SAW components for enhancing the sensor sensitivity. They have low time-bandwidth (TB) products of 2 and 11, respectively. We attained an improvement of the sensor sensitivity by factors of up to 20 compared to sensors employing non-dispersive SAW components.
elib2cris::1512001600,pankratz1998